Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Motor Matic Yamaha Fazzio Pada Dealer Yamaha Lautan Teduh Metro - Selamet Fuadi; Yateno; Willi Arda Bastiyan (Jurnal Manajemen DIVERSIFIKASI, 2025)
The development of the automotive industry in Indonesia is very fast and tends to increase every year, in line with the needs and demands of the public for adequate means of transportation. Evidenced by the increasingly crowded city streets and increasingly congested traffic by motorized vehicles. And followed by the birth and growth of new companies that always make every effort to gain and maintain existing market share. This study aims to find out 1) To find out whether there is an influence of product quality on consumer satisfaction? 2) to find out whether there is service quality on consumer satisfaction? 3) To find out whether there is an influence of product quality and service quality on consumer satisfaction? This study uses a quantitative approach. The survey method was chosen as the primary data source. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaire instrument or questionnaire. In this study, the population was consumers at the Honda Motor Palace dealership. The sampling technique used was accidental sampling with a total sample of 89 people. Data collection techniques using a questionnaire with a Likert scale. The results of the study show that: 1) there is a positive influence on product quality on consumer satisfaction. 2) there is a positive influence of service quality on consumer satisfaction. 3) there is a positive influence on product quality and service quality on consumer satisfaction.